PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE MODIFIKASI PADA PERUSAHAAN BUMN GO PUBLIC SEKTOR FARMASI DI INDONESIA - MAIYALIZA MAIYALIZA (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
This study aims to test the prediction of insolvency in the BUMNâ€™s farmation Company which listed on Indonesia Stock Exchange. The Altman Z-Score modification method used to see the prediction of companies bankruptcy in the 2008-2013 periods. The analysis technique used is the predictive model of Altman Z â€“ Score modification (1995, which it applies four variables X1 (working capital to total assets), X2 (retained earnings to total assets), X3 (earning before interest and tax to total assets), X4 (market value of equity to total liabilities). It has the formula Zâ€ = 6,56X1 + 3,26X2 + 6,72X3 + 1,05X4 within the Z â€“ Score assessment criteria Z â€“ Score < 1,1 is categorized bangkrupt companies. 1,1 < Z â€“ Score < 2,6 are in â€œgrey areaâ€. Z â€“ Score > 2,6 is categorized as a very healthy company. During the observations point start from 2008 to 2013 point out that PT Kimia Farma (Persero) Tbk categorized was â€œhealthyâ€ because its Z-score is above 2,6. While PT. Indofarma (persero) Tbk in 2008 â€“ 2010 positionedat â€œgrey areaâ€ category because of its Z â€“ Score was not reached up 2,6.Meanwhile in 2011 and 2012 were categorized as a healthy companies considered by its value of Z â€“ Score that reach 3,10 and 4,00. And 2013 the Z â€“ Score of PT Indofarma (persero) Tbk decreases againto be1,47. Over all, PT Indofarma (Persero) Tbk is categorized at the â€œgrey areaâ€ position.